Identifikasi Pengembangan Desa Wisata Berbasis Masyarakat Di Desa Tumaluntung Kecamatan Kauditan Kabupaten Minahasa Utara - Napitupulu, Anggi Maria Magdalena; Pangemanan, Lyndon Reindhart Jacob; Katiandagho, Theodora Maulina (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to identify and describe tourism potential, community-based tourism village development, and the five dimensions of community-based tourism development in Tumaluntung Village, Kauditan District, North Minahasa Regency. The research was conducted in September-November 2023 by collecting primary data through questionnaires and interviews with the Tourism Office, village government, Tourism Awareness Group, and local communities. Secondary data were obtained from various related sources. The research sample amounted to 43 respondents who were randomly selected. The results showed that Tumaluntung Village has natural and cultural tourism potential that has fulfilled the four main elements of tourism: attractions, accessibility, facilities, and institutions. Community participation is seen in the planning, implementation, and supervision stages of tourism village development. The success of community-based tourism is measured through five dimensions: economic, social, cultural, environmental, and political. However, the achievement of each indicator in these dimensions is still not optimal, especially in the economic aspect, because tourism activities are still not running actively. Several inhibiting factors include limited development funds, suboptimal management of tourism potential, lack of promotion, and low community participation in tourism management. In addition, village-owned enterprises and Tourism Awareness Groups have not played their role optimally, while accessibility and infrastructure in some attractions are still inadequate. Therefore, a better management strategy is needed to develop Tumaluntung Tourism Village in a sustainable manner.